2016
DOI: 10.1051/shsconf/20162303002
|View full text |Cite
|
Sign up to set email alerts
|

UHT Skim Coconut Milk Production and Its Quality

Abstract: The current study is based upon the potential value of low-fat coconut milk in market due to increasing health concerns in people nowadays. Skim coconut milk can be used as a food ingredient that requires coconut milk flavor but excluding fat. The fundamental objectives of this study were to examine the methods for skim coconut milk production and comparison of its quality with normal coconut milk. The results of this study indicated that the UHT skim coconut milk can be prepared by separating fat through a cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
2
5
1
Order By: Relevance
“…Coconut milk recorded 91.20 (L*-value), -1.10(a*-value) and 3.51 (b*-value). These results nearly were in agreement with Khuenpet et al (2016) who mentioned that coconut milk in Thailand had 78.21 L*-value, -0.40 a*-value and 3.68 b*-value.…”
Section: Samplessupporting
confidence: 92%
See 1 more Smart Citation
“…Coconut milk recorded 91.20 (L*-value), -1.10(a*-value) and 3.51 (b*-value). These results nearly were in agreement with Khuenpet et al (2016) who mentioned that coconut milk in Thailand had 78.21 L*-value, -0.40 a*-value and 3.68 b*-value.…”
Section: Samplessupporting
confidence: 92%
“…Corn milk had specific gravity 1.027 g/cm 3 , these result was in agreement with those of Ajala et al (2013), who found that corn milk (Freshly harvested) in Nigeria had specific gravity 1.03. Also specific gravity of coconut milk was 1.033 g/cm 3 , these result were higher than the values reported for coconut milk in Nigeria and Thailand (1.010 and 1.008 g/cm 3 , respectively) by Ladokun and Oni (2014); Khuenpet et al (2016). Meanwhile cantaloupe seed milk had specific gravity 1.024.…”
Section: Samplescontrasting
confidence: 55%
“…Negative effects of temperature on nutritional and sensorial quality of products. [121,138,[162][163][164]…”
Section: Fortification and Enrichmentmentioning
confidence: 99%
“…Several studies have reported application of sterilization treatments at 121 °C for 15-30 min in various non-dairy milks like almond, soy and peanut milks [20,81,84,85]. Also, UHT treatment in range of 134-140 °C for 2 to 20 seconds has been applied in different non-dairy milks like peanut, coconut and almond milk [69,86]. However, high temperature treatments have been reported to destabilize non-dairy milk alternative by resulting in coagulation of proteins.…”
Section: Heat Treatmentmentioning
confidence: 99%